Geomagnetic main field modeling with DMSP. Issue 5 (27th May 2014) - Alken, P.; Maus, S.; Lühr, H.; Redmon, R. J.; Rich, F.; Bowman, B.; O'Malley, S. M.
Abstract The Defense Meteorological Satellite Program (DMSP) launches and maintains a network of satellites to monitor the meteorological, oceanographic, and solar‐terrestrial physics environments. In the past decade, geomagnetic field modelers have focused much attention on magnetic measurements from missions such as CHAMP, Ørsted, and SAC‐C. With the completion of the CHAMP mission in 2010, there has been a multiyear gap in satellite‐based vector magnetic field measurements available for main field modeling. In this study, we calibrate the special sensor magnetometer instrument on board DMSP to create a data set suitable for main field modeling. These vector field measurements are calibrated to compute instrument timing shifts, scale factors, offsets, and nonorthogonality angles of the fluxgate magnetometer cores. Euler angles are then computed to determine the orientation of the vector magnetometer with respect to a local coordinate system. We fit a degree 15 main field model to the data set and compare with the World Magnetic Model and Ørsted scalar measurements. We call this model DMSP‐MAG‐1, and its coefficients and software are available for download at http://geomag.org/models/dmsp.html. Our results indicate that the DMSP data set will be a valuable source for main field modeling for the years between CHAMP and the recently launched Swarm mission.